The Effect of Green Intellectual Capital, Environmental Performance on Financial Performance with Green Strategy as Moderation - Nila Sari, Pratiwi; Fadhli Nursal, M. (Greenation International Journal of Economics and Accounting, 2024)
This study aims to determine the role of green strategy in moderating the effect of green intellectual capital and environmental performance on financial performance. This research uses energy sector companies during the 2019-2022 period. Sampling method with purposive sampling. The results of this study indicate that green intellectual capital, environmental performance individually does not affect company performance. Likewise with the role of green strategy which is not able to strengthen the influence of green intellectual capital, environmental performance does not affect company performance. However, the results of the tests carried out simultaneously showed that the results of green intellectual capital and environmental performance had an effect on company performance. There are implications in this research, namely for companies to be able to consider the environmental performance presented in sustainability reports, in order to be able to provide information not only on financial but also non-financial performance that encourages potential investors to invest in companies and for environmental sustainability. Regulators can provide international standards such as the GRI related to environmental performance disclosure to become a reference for companies. The limitations that researchers found when conducting this research are that there are several companies that have not published sustainability reports. In addition, the company also has not disclosed according to the 2021 GRI standards in its sustainability report.